Heterogeneous Zr solute segregation and Al3Zr dispersoid distributions in Al–Cu–Li alloys. (July 2015) - Tsivoulas, D.; Robson, J.D.
Abstract: During the homogenisation treatment of Al alloys the Al3 Zr phase is known to form heterogeneously in interdendritic areas where the Zr supersaturation is low. Several types of clusters were observed in the present Al–Cu–Li alloy. Although some clusters resemble the shape of the θ′-Al2 Cu lath-shaped particles, it is explained here that there is no direct nucleation on these particles and neither is Zr contained in them at amounts detectable via TEM-EDX. These planar arrays of Zr dispersoids were established to form via repeated precipitation on dislocations. Nucleation on dislocations was the dominant mechanism for individual Al3 Zr dispersoids also in the dendrite centre. This was explained on the grounds of the large atomic size misfit between Zr and the Al matrix which leads to segregation of the former atoms to dislocations and was verified experimentally by EDX. It is noteworthy that although Zr did not interact with the θ′ phase, it did so with the equilibrium θ phase and produced two different types of particles, one containing only Zr, and another having both Zr and Mn. It was also seen to be contained within Al20 Cu2 Mn3 dispersoids in agreement with previous findings.